High frequency of toxigenic Clostridium difficile and Clostridium perfringens coinfection among diarrheic patients at health care facility-onset (HCFO) and community-onset (CO) centers in Bogotá, Colombia (2019)
Background: The aim of this study was to evaluate the frequency of toxigenic C. difficile and C. perfringens infections at health care facility-onset (HCFO) and community-onset (CO), in two health care centers (HCC) in Bogotá, Colombia. A total of 220 stool samples from patients presenting diarrhea acquired at HCFO or CO were analyzed by several PCR tests. Results: We found that 65.5% (n = 144) of the population had C. difficile infection, followed by toxigenic C. difficile with 57.3% (n = 126), and finally toxigenic C. perfringens with a frequency of 32.7% (n = 72). Conclusions: This study is the first molecular detection and characterization of C. difficile and C. perfringens in HCFO and CO in Latin America and demonstrates a relevant frequency of these two species, including coinfection and strikingly diverse toxigenic profiles, especially in the CO. © 2019 The Author(s).